MANAJEMEN KURIKULUM DAN PEMBELAJARAN DI SEKOLAH MENENGAH: TREN DAN IMPLEMENTASI DI INDONESIA - Hasbullah Hasbullah (Berajah Journal, 2026)
This study examines curriculum and learning management in secondary schools, focusing on development trends and their implementation in Indonesia. The study is motivated by changes in education policy that require schools to be more adaptive, flexible and learner-centred. Curriculum management is understood not only as the organisation of academic documents, but also as an interrelated process of planning, implementation, evaluation and development of learning. In the Indonesian context, the implementation of the Merdeka Curriculum represents a form of educational reform that emphasises differentiated learning, the strengthening of competencies, and school autonomy in managing the operational curriculum. The method employed in this study is a literature review, examining various scholarly sources such as journal articles, books, and relevant policy documents. The findings indicate that trends in curriculum management in secondary schools are moving towards more active, competence-based learning supported by the use of digital technology. However, its implementation still faces challenges regarding teacher readiness, limited facilities and infrastructure, and disparities in capacity between schools. Therefore, the success of curriculum management and learning depends heavily on synergy between headteachers, teachers, students, and educational policy support. Consequently, strengthening human resource capacity and improving support systems are crucial factors in enhancing the quality of secondary education in Indonesia.